New Network Architectures The Path to the Future Internet - Tronco, Tania; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"Future Internet" is a worldwide hot topic. The Internet has become a critical infrastructure for business development and social interactions. However, the immense growth of the Internet has resulted in additional stresses on its architecture, resulting in a network difficult to monitor, understand, and manage due to its huge scale in terms of connected devices and actors (end users, content providers, equipment vendors, etc). This book presents and discusses the ongoing initiatives and experimental facilities for the creation of new Future Internet Architectures using alternative approaches like Clean Slate and Incremental improvements: It considers several possible internet network use scenarios that include seamless mobility, ad hoc networks, sensor networks, internet of things and new paradigms like content and user centric networks.
A Brief History of the Internet -- Principles of Internet Architecture -- Evolution of Internet Architecture -- Scenarios of Evolution for a Future Internet Architecture -- Future Network Architectures: Technological Challenges and Trends -- New Generation Internet Architectures: Recent and Ongoing Projects -- OneLab: An Open Federated Facility for Experimentally Driven Future Internet Research -- RNP Experiences and Expectations in Future Internet Research and Development -- Description of Network Research Enablers on the Example of OpenFlow -- Re-architected Cloud Data Center Networks and Their Impact on the Future Internet -- Improving the Scalability of Internet Routing -- Delivering Building Blocks for Internet of Services: Trust, Security, Privacy and Dependability -- ITU Focus Group on Future Networks -- Key Issues on Future Internet -- Challenges for the Brazilian Green and Yellow Internet.
Keywords: Engineering; Computer Communication Networks; Telecommunication; Engineering; Communications Engineering, Networks; Computer Communication Networks